The Effect of Clarity on Budgetary Targets and Organizational Culture on Government Agencies' Performance Accountability at Aceh Besar District Government Offices - Radhiana; T. Andi Roza (Nur Science Institute, 2022)
This research is an empirical study that aims to determine the effect of clarity on budget targets and organizational culture both jointly and partially on agency performance accountability at the Aceh Besar District Government Office. The population in this study were all financial management officials at 21 SKPDs in the Aceh Besar District Government, consisting of secretaries, heads of finance sub-divisions and treasurers, totaling 81 people. Because the total population is less than 100, the entire population is used as a sample. Data collection was carried out by distributing closed questionnaires that had been prepared to the respondents. Primary data were analyzed using multiple linear regression. The results of the study explain that both jointly and partially the clarity of budget targets and organizational culture influence the performance accountability of government agencies at the Aceh Besar District Government Office with an influence value of 0.621 and 0.290 respectively. The R value of 0.620 or 62.00% explains that there is a positive and strong relationship between the clarity of budget targets and organizational culture with Government Agency Performance Accountability at the Aceh Besar District Government Office. The value of R Square (R2) is 0.384, meaning that the ability of the two independent variables to explain the dependent variable is 38.40%. While the remaining 61.60% is influenced by other variables not included in this research model.